Wellens' syndrome in a 24-year-old woman. (30th April 2013) - Khan, Beenish; Alexander, John; Rathod, Krishnaraj Sinhji; Farooqi, Fahad
Abstract : Wellens' syndrome refers to specific ECG abnormalities in the precordial T-wave segment, which are associated with critical stenosis of the proximal left anterior descending (LAD) coronary artery culminating in an acute anterior wall myocardial infarction (MI) if the patient is not urgently revascularised. We describe the youngest reported presentation of Wellens' syndrome in a 24-year-old woman with unstable chest pain, characteristic ECG changes and slight troponin biomarker elevation. This was initially unrecognised by the emergency department as unstable coronary syndrome and she subsequently progressed to an anterior non-ST elevation MI (NSTEMI). Her coronary angiogram showed critical narrowing of the proximal LAD which was successfully treated with a drug-eluting stent.